2012
DOI: 10.3171/2012.9.focus12278
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional alterations in sports concussion

Abstract: In this review the authors discuss persistent and cumulative alterations in both cognitive and motor function after sports concussions detected with some of the newest, most sophisticated brain investigation techniques. Ranging from subclinical neurophysiological alterations in young concussed athletes to quantifiable cognitive and motor function declines in former athletes in late adulthood with concussions sustained decades earlier, this review is also intended to provide new insights into the neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 66 publications
5
37
2
Order By: Relevance
“…This hypothesis is consistent with recent literature showing persistent motor dysfunctions following concussion (De Beaumont et al, 2012). For example, postural stability is now increasingly used as part of post-concussion return-to-play protocols (Harmon et al, 2013) as a growing body of evidence suggests the presence of balance deficits following injury (Guskiewicz, 2001a,b; Cavanaugh et al, 2005; Parker et al, 2006).…”
Section: Introductionsupporting
confidence: 94%
“…This hypothesis is consistent with recent literature showing persistent motor dysfunctions following concussion (De Beaumont et al, 2012). For example, postural stability is now increasingly used as part of post-concussion return-to-play protocols (Harmon et al, 2013) as a growing body of evidence suggests the presence of balance deficits following injury (Guskiewicz, 2001a,b; Cavanaugh et al, 2005; Parker et al, 2006).…”
Section: Introductionsupporting
confidence: 94%
“…Previous research has demonstrated that, in 90% of cases, symptoms abate within 7-10 days of concussion onset [2]. However, using the resolution of symptoms as an indicator of an athlete's readiness to return to play is problematic as sub-clinical neurophysiological deficits may still exist (for review see De Beaumont et al [3]). …”
Section: Introductionmentioning
confidence: 98%
“…Indeed, from a clinical perspective, sports concussion has been associated with an increased risk of clinical depression [9,10], chronic traumatic encephalopathy [3], Alzheimer's disease [11] and premature ageing [12]. Additionally, there is mounting neurophysiological evidence of cumulative effects of concussions on cognitive functions [13][14][15][16][17] and motor system functioning [18,19] that persist in time [20,21].…”
Section: Introductionmentioning
confidence: 99%